2004
DOI: 10.4049/jimmunol.172.10.6460
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Galactose-α-1,3-Galactose Expression on Porcine Endothelial Cells Prevents Complement-Induced Lysis but Not Direct Xenogeneic NK Cytotoxicity

Abstract: The galactose-α-1,3-galactose (αGal) carbohydrate epitope is expressed on porcine, but not human cells, and therefore represents a major target for preformed human anti-pig natural Abs (NAb). Based on results from pig-to-primate animal models, NAb binding to porcine endothelial cells will likely induce complement activation, lysis, and hyperacute rejection in pig-to-human xenotransplantation. Human NK cells may also contribute to innate immune responses against xenografts, either by direct recognition of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 62 publications
7
64
3
Order By: Relevance
“…6) and displayed an EC-typical phenotype including the expression of adhesion receptors important for human leukocyte adhesion (24). The observations that the immortalized cells in this study showed the same results as the primary PAECs, lends support to the validity of previous results obtained using these cell lines as a reliable model for in vitro studies on the role of Gal in pig-to-human xenotransplantation (16,24,45), where the immortalized Gal Ϫ/Ϫ were used. The fact that immortalized and primary Gal ϩ/ϩ PAEC induced comparable cytokine production patterns in human cells, except for only three cytokines (IFN-␥, TNF-␣, and VEGF) exclusively detected when using immortalized cells, support the assumption that the primary and immortalized cells differ only slightly phenotypically, and that these cytokines might not be physiologically relevant in a clinically setting.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…6) and displayed an EC-typical phenotype including the expression of adhesion receptors important for human leukocyte adhesion (24). The observations that the immortalized cells in this study showed the same results as the primary PAECs, lends support to the validity of previous results obtained using these cell lines as a reliable model for in vitro studies on the role of Gal in pig-to-human xenotransplantation (16,24,45), where the immortalized Gal Ϫ/Ϫ were used. The fact that immortalized and primary Gal ϩ/ϩ PAEC induced comparable cytokine production patterns in human cells, except for only three cytokines (IFN-␥, TNF-␣, and VEGF) exclusively detected when using immortalized cells, support the assumption that the primary and immortalized cells differ only slightly phenotypically, and that these cytokines might not be physiologically relevant in a clinically setting.…”
Section: Discussionsupporting
confidence: 76%
“…The immortalized PAEC line PEDSV.15 (Gal ϩ/ϩ ) was generated as previously described in detail (27). The Gal Ϫ/Ϫ cell line PED2*3.51 was generated from PEDSV.15 by homologous recombination, panning, and limiting dilution cloning (28). All cells were cultured in DMEM (Invitrogen Life Technologies) supplemented with 10% FCS (BioWhittaker), 1 mM sodium pyruvate, 2 mM L-glutamine, 0.1 mM nonessential amino acids, 20 mM HEPES, 50 g/ml gentamicin (all obtained from Invitrogen Life Technologies), and 0.25 g/ml amphotericin B (BioWhittaker).…”
Section: Cell Culturementioning
confidence: 99%
“…It is unclear whether the preformed SLs are sufficient or the de novo formation of SLs is necessary for their lytic function. PECs have been widely used to activate xenogeneic NK cytotoxicity (20). When NK cells were allowed to drop onto a monolayer of PECs for 10 min, we observed a large augmentation in the secretory response elicited by Ca 2ϩ , as shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The GalT- KO modification of pigs overcomes acute humoral rejection, but provides no advantage in preventing graft destruction by NK cells (either by direct or by indirect mechanisms). This presents an impending barrier to organ and cellular xenotransplantation, because the recognition of pig cells by NK cells is not dependent on the expression of Gal [35]. Being non-vascularized grafts, direct mechanisms are involved in the destruction of xenogeneic hepatocytes.…”
Section: Natural Killer (Nk) Cellsmentioning
confidence: 99%